Study on Competitiveness of Mongolian Coking Coal - Purev, Bolortuya; He, Weida (Technium Social Sciences Journal, 2021)
Mongolia is one of the richest countries in coal reserves. It ranks seventh in the world In terms of its coal reserves and first in terms of per capita reserves. Coal reserves are relatively evenly distributed in Mongolia. 2% of the total coal reserves are anthracite, 31% are hard coal and 67% are lignite. The mining sector plays an important role in the economy of Mongolia. As of 2019, the mining sector produced 25% of Mongolia's gross domestic product, 74% of total industrial products, and about 90% of export products. In Mongolia, about 90% of coals mined for the energy purpose is used as the fuel for thermal power plants. Mongolia exports most of its coking coal to China. Steel production of China is growing every year and the demand for coking coal is increasing, which is having a positive effect on the Mongolian economy. China is the closest market to Mongolia. This article studies the world's coal reserves, market outlook, the current situation and future prospects of Mongolia's coal sector, coking coal production of China, demand and supply, coal sector strategy of Mongolia, and opportunities to improve the competitiveness of the coking coal market.